Breakfast Intake and Composition Is Associated with Superior Academic Achievement in Elementary Schoolchildren. (18th May 2016) - Ptomey, Lauren T.; Steger, Felicia L.; Schubert, Matthew M.; Lee, Jaehoon; Willis, Erik A.; Sullivan, Debra K.; Szabo-Reed, Amanda N.; Washburn, Richard A.; Donnelly, Joseph E.
Abstract : Objective : To determine whether breakfast consumption or content affects academic achievement measured by standardized tests. Methods : Baseline data were collected in fall of 2011 from 698 students (50.5% female, age = 7.5 ± 0.6 years) living in the state of Kansas. Academic achievement was assessed using 3 components from the Wechsler Individual Achievement Test (WIAT-III). Prior to taking the WIAT-III, participants completed a breakfast recall of all foods and drinks consumed that morning, which was analyzed using Nutrition Data System for Research (NDS-R). WIAT-III scores were compared between breakfast and non-breakfast consumers in a sample ( n = 162) matched for age, sex, race, education level of both parents, household income, body mass index (BMI), and cardiovascular fitness, and Pearson correlations were calculated from all breakfast eaters ( n = 617) between test performance and components of the breakfast. Results : When compared to non-breakfast consumers, the breakfast consumers had significantly higher scores in all 3 WIAT-III components (all p < 0.05). In breakfast consumers, servings of fruit juice were negatively correlated with reading comprehension and fluency standard score and mathematics standard score (both p < 0.0001), and greater servings of whole grains were significantly related to higher scores in reading comprehension and fluency and mathematics (both p < 0.05). Conclusion : Both breakfast consumption and the content may be associated with improved standardized test performance in elementary school students.